Membangun Kesejahteraan Pikiran untuk Kesehatan Mental Melalui Gaya Hidup Sehat dan Olahraga - Ramdani, Raihan Fajar; Herlambang, Akbar Dwi; Falhadi, Mufti Malik; Fadilah, Muhamad Zaki; Turnip, Crist Evan Lamhot; Mulyana, Agus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Mental health is a major concern amid fast-paced and stressful modern life. A healthy lifestyle and exercise have been shown to play an important role in building optimal mental well-being and mental health. This article presents a comprehensive literature review of the relationship between healthy lifestyles, exercise, and the well-being of the mind. This study uses a qualitative approach through a comprehensive literature review as the main method. Literature reviews are used to use information from various sources such as scientific journals, books, and online articles that are relevant to the research topic. The triangulation approach is also used in data collection and analysis. The results of the analysis showed that regular exercise can improve mood, reduce stress, and improve overall psychological well-being. In addition, a healthy lifestyle, including a balanced diet, stress management, and social support, also plays an important role in maintaining mental health. Considering findings from related research and support from various sources, this article highlights the importance of paying attention to mental health through healthy lifestyle practices and exercise.